Factors That Influence On The Price To Book Value Of The Company In Indonesia Stock Exchange - Sanjaya, Riki; Henviani, Henviani (Kesatuan Press, 2020)
The purpose of this research is to examine institutional ownership, profitability, liquidity, dividend policy, debt policy, firm size, audit committee, managerial ownership in affecting price to book value in non-financial companies listed in Indonesia Stock Exchange. This research used 54 listed non-financial companies in Indonesia Stock Exchange, and the data were selected using a purposive sampling method during the research period 201 6 until 2018. Data were analyzed using multiple regression methods. The research results show that profitability and debt policy had a significant influence on price to book value. In contrast, for institutional ownership, liquidity, dividend policy, firm size, audit committee, managerial ownership had no considerable influence on price to book value.